Playing for Pizza - Grisham, John. (New York : Bantam Dell, 2012)
After providing what is arguably the worst single performance in the history of the NFL, third-string quarterback Rick Dockery becomes a national laughingstock. Cut by the Cleveland Browns, and shunned by every other team, Rick insists that his agent find a team that "does" need him. Against enormous odds, Rick lands a job--as the "starting "quarterback for the Mighty Panthers . . . of Parma, Italy. The Parma Panthers desperately want a former NFL player--any former NFL player--at their helm. And now theyve got Rick, who knows nothing about Parma (not even where it is) and doesnt speak a word of Italian. To say that Italy--the land of fine wines, extremely small cars, and "football americano"--holds a few surprises for Rick Dockery would be something of an understatement.
880
Accelerated Reader/Renaissance Learning
Keywords: Americans -- Italy; Fiction; Novels